‘This Realm of England is an Empire’ - Ullmann, Walter (The journal of ecclesiastical history, 1979)
Few phrases in an English Statute can have left such an indelible imprint as the opening words of the Act in Restraint of Appeals of 1533: they have evoked a literature of their own. If on this occasion a mere medievalist has the temerity to enter the precincts of the Henrician Reformation measures it is not because he is unaware of the pitfalls that may be in store for him, but because he believes that an exegesis which sets these famous words in their strictly confined historical context may possibly contribute to a better comprehension of the matrix of what came to be the Ecclesia Anglicana of the Reformation era. In offering the jubiland a modest essay on this topic, I hope he will accept it in the spirit in which it is submitted to him: as a token of gratitude for the services he has conspicuously rendered to ecclesiastical history. Specifically, this brief sketch is to pay respect to Clifford Dugmore as the parent and editor of the JEH which for long will remain a monument to his initiative, courage and perseverance: he has tended his own creation in an exemplary way for 30 years and saw the Journal grow to an internationally acknowledged organ of ecclesiastical history. It is a self-evident duty to pay tribute, however inadequate it may be, to his single-minded devotion to historical scholarship and dedicated editorship. Rarely can an occasion so clearly have offered a three-fold cause for rejoicing: the celebration of his seventieth birthday, the celebration of the thirtieth birthday of the JEH, and the conclusion of thirty years of his editorship. Quid plura?